Caracterización de los factores autoevaluacion, autorregulacion y bienestar institucional en la institucion tecnica profesional frente al sistema de acreditacion Colombiano (2017)
In the reflective exercise of the impact of institutional accreditation in the strengthening of the factors of self-assessment and self-regulation processes and institutional welfare in the higher education institution INFOTEP, it seeks to determine those situations, activities, subjects and processes that guide the course of the application of these in the improvement of academic administrative activities. The study aims to characterize the self-assessment and self-regulation factors and the behavior of INFOTEP's institutional welfare processes, as opposed to the guidelines of the national accreditation system, taking as an example the institutions of higher education accredited in the Colombian Caribbean region, in the environments of accreditation based on the experiences of the same in all the lines of its operation that point to the academic and institutional accreditation.